Prospective double-blind randomised controlled trial protocol comparing bone marrow aspirate concentrate intra-articular injection combined with subchondral injection versus intra-articular injection alone for the treatment of symptomatic knee osteoarthritis. Issue 9 (8th September 2022) - Silva, Simone; Andriolo, Luca; Boffa, Angelo; Di Martino, Alessandro; Reale, Davide; Vara, Giulio; Miceli, Marco; Cavallo, Carola; Grigolo, Brunella; Zaffagnini, Stefano; Filardo, Giuseppe
Abstract : Introduction: Subchondral and intra-articular injections of bone marrow aspirate concentrate (BMAC) showed promising results for knee osteoarthritis (OA) patients. To date, there is no evidence to demonstrate whether the combination of these treatments provides higher benefits than the intra-articular injection alone. Methods and analysis: Eighty-six patients with symptomatic knee OA (aged between 40 and 70 years) are randomised to BMAC intra-articular injection combined with subchondral BMAC injection or BMAC intra-articular injection alone in a ratio of 1:1. The primary outcome is the total Western Ontario and McMaster Universities Osteoarthritis Index, the secondary outcomes are the International Knee Documentation Committee Subjective and Objective Knee Evaluation Form, the Tegner activity scale, the EuroQol-Visual Analogue Scale, and the health questionnaire European Quality of Life Five Dimension score. Additional CT and MRI evaluations are performed at the baseline assessment and at the final 12-month follow-up. The hypothesis is that the combined injections provide higher knee pain and function improvement compared with BMAC intra-articular injection alone. The primary analysis follows an intention to treat principle. Ethics and dissemination: The study protocol has been approved by the Emilia Wide Area Ethical Committee of the Emilia-Romagna Region (CE-AVEC), Bologna, Italy. Written informed consent is obtained from all the participants. Findings of this study will be disseminated through peer-reviewed publications and conference presentations. Protocol version: Version 1 (14 May 2018). Trial registration number: NCT03876795 .